Modern Vehicle Access Control Technologies at Industrial Facilities - Nagovitsyn, K. O. (ХНУРЕ, 2025)
The article explores the use of modern access control technologies for vehicles in industrial environments. It focuses on two of the most widespread solutions – automatic number plate recognition (ANPR) and radio frequency identification (RFID). These technologies are analyzed in terms of their working principles, integration capabilities, and operational efficiency. The study highlights their practical benefits in logistics, security, and automation, while also pointing out technical and implementation-related challenges. The results provide insight into how such systems contribute to improving the safety and efficiency of industrial transport access management.
Keywords: ANPR; RFID; access control; vehicle identification; industrial infrastructure